2000
DOI: 10.1074/jbc.275.10.7321
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Amino Acid Residues in the Active Site ofEscherichia coli Pyrroloquinoline Quinone-Containing Quinoprotein Glucose Dehydrogenase

Abstract: Several mutants of quinoprotein glucose dehydrogenase (GDH) in Escherichia coli, located around its cofactor pyrroloquinoline quinone (PQQ), were constructed by site-specific mutagenesis and characterized by enzymatic and kinetic analyses. Of these, critical mutants were further characterized after purification or by different amino acid substitutions. H262A mutant showed reduced affinities both for glucose and PQQ without significant effect on glucose oxidase activity, indicating that His-262 occurs very clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…In this study, we identified amino acid residues interacting with bound UQ and proposed their functions in intramolecular events of the enzyme. Clues for this issue have been obtained by previous studies that revealed very close location of the bound UQ to PQQ (31) and the position and functions of Asp-466 and Lys-493 flanking PQQ (11). Site-directed mutants of Asp-354, Asp-466, and Lys-493 had significant effects on the characteristics of UQ semiquinone radicals or UQ EPR signals and/or the affinity for UQ.…”
mentioning
confidence: 99%
“…In this study, we identified amino acid residues interacting with bound UQ and proposed their functions in intramolecular events of the enzyme. Clues for this issue have been obtained by previous studies that revealed very close location of the bound UQ to PQQ (31) and the position and functions of Asp-466 and Lys-493 flanking PQQ (11). Site-directed mutants of Asp-354, Asp-466, and Lys-493 had significant effects on the characteristics of UQ semiquinone radicals or UQ EPR signals and/or the affinity for UQ.…”
mentioning
confidence: 99%
“…6). Pulse radiolysis analysis revealed that the two redox centers are closely located at a distance of 11-13 Å and that Asp466 and Lys493 are involved in proton donation to the semiquinone anion radical of bound Q and in electron transfer from bound UQ to PQQ, respectively (Elias et al, 2000;Mustafa et al, 2008a). Recent mGDH analysis provided the first evidence that the primary dehydrogenase in respiratory chains utilizes both MK and UQ as a bound Q and suggest that bound MK occurs in a fashion similar to that of bound UQ in the mGDH molecule and functions as an electron acceptor from PQQ (Mustafa et al, 2008b).…”
Section: Menaquinone As Well As Uq As a Bound Quinone Is Crucial For mentioning
confidence: 99%
“…Glucose oxidase activity of membrane fractions (coupling ability of GDH to an electron transport chain in the membrane) was determined using an oxygen electrode as described previously (13,32). Q-2 reductase activity was measured spectrophotometrically as described previously (13). One unit of PMS reductase or Q-2 reductase activity is defined as 1 mol of dichloroindophenol or Q-2, respectively, reduced/ min, both of which correspond to 1 mol of glucose oxidized/min.…”
Section: Treatment Of Membrane Fraction With a High Salt Or Mildmentioning
confidence: 99%
“…Using the holo-enzyme thus prepared, the following enzyme activities were measured. PMS reductase activity was measured spectrophotometrically (U-2000A, Hitachi) with PMS and dichloroindophenol as an electron mediator and acceptor, respectively, as described previously (13,32). Glucose oxidase activity of membrane fractions (coupling ability of GDH to an electron transport chain in the membrane) was determined using an oxygen electrode as described previously (13,32).…”
Section: Treatment Of Membrane Fraction With a High Salt Or Mildmentioning
confidence: 99%
See 1 more Smart Citation